The Profile of Students’ Errors in Constructing Mathematical Concepts on Gcd and Lcm Topics in Grade VII Junior High School Based on Cognitive Styles - Ririn Sundari Dewi Pratiwi; Rita Lefrida; Mubarik Mubarik; Sukayasa Sukayasa (Journal of Educational Sciences, 2026)
This study aims to describe students’ errors in constructing mathematical concepts when solving problems on GCD and LCM, viewed from their cognitive styles. This study employed a descriptive qualitative approach. Two students were selected as research subjects based on the results of the Group Embedded Figures Test (GEFT), each representing the Field Independent (FI) and Field Dependent (FD) cognitive styles. Data were collected through tasks on GCD and LCM, followed by interviews. The data were analyzed using an iterative model, consisting of data condensation, data display, and conclusion drawing. The research findings indicate that FD students make a wider variety of errors compared to FI students. Pseudo Construction was the most dominant type of error in both subjects, indicating a discrepancy between students’ conceptual understanding and their written answers. In addition, FD students showed incomplete conceptual structures and difficulties in using analogies, whereas FI students tended to experience more errors in logical reasoning. Thus, it can be concluded that differences in cognitive styles influence the types and complexity of students’ concept construction errors; therefore, learning strategies that emphasize conceptual understanding and are adapted to students’ cognitive characteristics are needed.